A virtual exhibition system for the National Archives of Singapore. - Lim, Johanna Chua. (2008)
The main tasks of the project are to determine appropriate metadata models for virtual exhibitions and the different digital artifacts, develop an efficient method of creating virtual exhibitions, and implement a facility for searching the textual content of virtual exhibitions and digital artifacts. It becomes a simple task to create new Web-based virtual exhibitions in HTML format.